The Rule of Law in the Liberal Script: Central Commitments, Variations, and Contestations - Mattias Kumm (The Liberal Script at the Beginning of the 21st Century: Conceptions, Components, and Tensions, 2024)
The commitment to the rule of law as an ideal is central to the liberal script, yet its meaning remains contested. Those contestations relate both to the distinctive point of the ideal and the more concrete features it requires. The point of the ideal, this chapter argues, is not only to highlight the virtues of laws formalities, but to articulate the conditions that must be met in order for law to actually have the authority it claims to have. What those conditions are is also disputed. It is possible to distinguish between classical and neoliberal interpretations, republican interpretations and constitutionalist interpretations of the rule of law, with the last having the strongest arguments on its side.
Keywords: 340; rule of law; legitimate authority; republicanism; constitutionalism; neoliberalism; classical liberalism; human rights; democracy